Habitação de emergência: a sociedade civil organizada como catalisadora de transformações no atendimento público às famílias em situação de vulnerabilidade no município de São Paulo - Escudero, Indalécia Sergia Almeida Brandão (2020)
The outlook for vulnerable populations is worrying and growing, especially in large cities. This research seeks to compose authors who can collaborate in the construction of a more just and egalitarian society, through the insertion in urban planning of a typology of emergency housing, as part of the governmental and corporate social responsibility actions that assist families in situations of extreme poverty. This research, using a qualitative method, analyzes the trajectory and action of the non-governmental organization TETO in Brazil. TETO operates throughout Latin America, building emergency housing with the collaboration of young volunteers engaged in social equality. Present in Brazil since 2009, its purpose is to carry out humanitarian actions with the collaboration of the workforce of young volunteers to promote social development and empowerment of vulnerable families. In this context, the research question that leads the present study arose: How can TETO, which works in the construction of emergency housing, act as an intermediary entity between the government and the population in a situation of vulnerability? The sub-questions that will guide this case study are related to the themes: How has TETO's role evolved in relation to government programs in Chile? What practices involve this role, currently and historically? How do these practices allow an alliance between organized civil society and the municipality?